Greek Isaiah 13:1-14:23: Translation technique and literary structure - Albanese, MJ (2022)
In this thesis, I pursue a translation technical analysis of the oracle against Babylon and her king in Greek Isaiah 13:1-14:23 from two distinct perspectives. First, in the vein of Septuagint translation technique, I survey specific examples from these two chapters and highlight their literary and stylistic features. Second, I explore these same chapters at the levels of literary macro- and micro-structure, highlighting the translator’s awareness of the Hebrew text’s own literary structure and his appropriation of such features into the Greek. In this analysis, I demonstrate that ‘free’ renderings in Greek Isaiah serve the purpose of explicating and heightening the literary and structural features latent in the Hebrew text. Thus, the constructed Greek text largely derived its coherence from the Hebrew text itself. Even though some features of Greek Isaiah arose without literary or structural motivations, the large number of translation features originating in the Hebrew text illustrates the literary and structural emphases with which the translator approached his work.